2019
DOI: 10.1002/qj.3573
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the role of individual diabatic processes for the formation of PV anomalies in a North Pacific cyclone

Abstract: Processes that do not conserve potential vorticity (PV) have a profound impact on the intensity, evolution, and mesoscale details of extratropical weather systems. This study aims at quantifying and improving the understanding of how and when physical processes modify PV in cyclones. To this end, a 6-day forecast of a North Pacific cyclone is performed using a recent operational version of the ECMWF global numerical weather prediction model. Hourly instantaneous temperature and momentum tendencies of each para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 76 publications
(107 reference statements)
4
50
0
Order By: Relevance
“…Our sensitivity experiments corroborate earlier studies that the interaction between mobile synoptic-scale eddies and planetary-scale flow anomalies plays an important role for blocking formation and maintenance (Nakamura et al, 1997;Luo et al, 2014;Nakamura and Huang, 2018), and show that diabatic processes can provide the required flow amplification in addition to dry-dynamical forcing. In order to properly represent blocking dynamics, numerical weather prediction and climate models thus have to correctly account for this coupling between dry and moist processes, including the details of microphyical processes that shape the spatial distribution of latent heating in clouds (e.g., Joos and Wernli, 2012;Dearden et al, 2016;Joos and Forbes, 2016;Crezee et al, 2017;Attinger et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our sensitivity experiments corroborate earlier studies that the interaction between mobile synoptic-scale eddies and planetary-scale flow anomalies plays an important role for blocking formation and maintenance (Nakamura et al, 1997;Luo et al, 2014;Nakamura and Huang, 2018), and show that diabatic processes can provide the required flow amplification in addition to dry-dynamical forcing. In order to properly represent blocking dynamics, numerical weather prediction and climate models thus have to correctly account for this coupling between dry and moist processes, including the details of microphyical processes that shape the spatial distribution of latent heating in clouds (e.g., Joos and Wernli, 2012;Dearden et al, 2016;Joos and Forbes, 2016;Crezee et al, 2017;Attinger et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…LH is artificially turned off by multiplying the instantaneous temperature tendencies due to parameterized cloud and convection processes with a factor α = 0.0, but still allowing for moisture changes due to cloud and precipitation formation. Other non-conservative processes, such as radiative heating and turbulent mixing, which can also modify PV (Spreitzer et al, 2019;Attinger et al, 2019), are not altered. In contrast to previous studies, here LH is only modified in the region that is identified to be directly relevant for the blocking system, which is typically the WCB ascent region associated with upstream extratropical cyclones (Steinfeld and Pfahl, 2019).…”
Section: Sensitivity Experimentsmentioning
confidence: 99%
“…The WCB case study was simulated with the limited-area nonhydrostatic model COSMO (Consortium for Small-scale Modeling; Baldauf et al, 2011;Doms and Baldauf, 2018) at 0.02 • (≈ 2.2 km) horizontal grid spacing with 60 vertical levels. The setup of the COSMO simulation and the online trajectories was the same as in Oertel et al (2019).…”
Section: Data and Approach 21 Cosmo Setup And Trajectoriesmentioning
confidence: 99%
“…Initial and lateral boundary conditions are taken from the ECMWF analyses with a horizontal resolution of 0.1 • every 6 h. The domain is centered in the eastern North Atlantic and extends from about 50 • W to 20 • E and 30 to 70 • N. We apply the standard COSMO setup of the Swiss National Weather Service, which employs a one-moment six-category cloud microphysics scheme including prognostic water vapor (q v ), liquid (LWC) and ice (IWC) cloud water content, rain (LWC), snow (SWC), and graupel (GWC). The graupel category is important for the explicit simulation of deep convection (Baldauf et al, 2011). Deep convection is resolved at 2.2 km (e.g., Ban et al, 2014), while for shallow convection the reduced Tiedtke scheme was applied (Tiedtke, 1989;Baldauf et al, 2011).…”
Section: Data and Approach 21 Cosmo Setup And Trajectoriesmentioning
confidence: 99%
See 1 more Smart Citation